2021
DOI: 10.1080/22221751.2021.1899054
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism regulating the differential expression of the P28-OMP outer membrane proteins in obligatory intracellular pathogen Ehrlichia chaffeensis

Abstract: Ehrlichia chaffeensis causes human monocytic ehrlichiosis (HME), which is one of the most prevalent, life-threatening emerging infectious zoonoses. The life cycle of E. chaffeensis includes ticks and mammals, in which E. chaffeensis proteins are expressed differentially contributing to bacterial survival and infection. Among the E. chaffeensis P28-OMP outer membrane proteins, OMP-1B and P28 are predominantly expressed in tick cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Southwestern blot analysis revealed DNA-protein interactions of the promoters of p28-Omp14 and p28-Omp19 with Tr1, MerR and EcxR proteins ( Figure 1 A). As previous reports demonstrated similar EcxR and Tr1 interactions with additional gene promoters [ 24 , 25 ], we extended the Southwestern blot experiments of EcxR and Tr1 with four additional E. chaffeensis promoters of genes tr1, clpB, groES/L and dnaK. Three of these gene promoters (clpB, groES/L and dnaK) were selected as they belong to the genes encoding for the molecular chaperonin family engaged in the bacterial stress response and are transcribed by RNA polymerase containing the stress response sigma factor; σ 32 [ 35 , 36 , 37 ], while Tr1 is included as a prior study reported that it is autoregulated by Tr1 protein and by EcxR [ 25 ].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Southwestern blot analysis revealed DNA-protein interactions of the promoters of p28-Omp14 and p28-Omp19 with Tr1, MerR and EcxR proteins ( Figure 1 A). As previous reports demonstrated similar EcxR and Tr1 interactions with additional gene promoters [ 24 , 25 ], we extended the Southwestern blot experiments of EcxR and Tr1 with four additional E. chaffeensis promoters of genes tr1, clpB, groES/L and dnaK. Three of these gene promoters (clpB, groES/L and dnaK) were selected as they belong to the genes encoding for the molecular chaperonin family engaged in the bacterial stress response and are transcribed by RNA polymerase containing the stress response sigma factor; σ 32 [ 35 , 36 , 37 ], while Tr1 is included as a prior study reported that it is autoregulated by Tr1 protein and by EcxR [ 25 ].…”
Section: Resultssupporting
confidence: 78%
“…E. chaffeensis genome encodes for a limited number of predicted transcription regulators; EcxR (ECH_0795), CtrA (ECH_1012), HU (ECH_0804), MerR (ECH_0163) and Tr1 (ECH_1118). Recent studies identified EcxR, CtrA and Tr1 as functional transcriptional regulators in E. chaffeensis [ 23 , 24 , 25 ]. EcxR and its homologs ApxR in A. phagocytophilum and ErxR in Ehrlichia ruminantium are partially characterized [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted from each sample and reverse transcribed to cDNA as described previously ( Duan et al, 2021 ). The amounts of E. chaffeensis 16S rRNA, ctrA , gshA , gshB , p28 , and human GAPDH were determined with qRT-PCR using specific primers ( Supplementary Table S1 ) and the ChamQ Universal SYBR qPCR Master Mix (Vazyme, Nanjing, China) on a StepOnePlus™ Real-Time PCR System (Applied Biosystems, MA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced green fluorescent protein fusions were constructed as described previously ( Duan et al, 2021 ). Briefly, the promoter region of gshA , gshB , or p28 was amplified and inserted upstream of the promoter-less egfp gene in the pQE60 vector.…”
Section: Methodsmentioning
confidence: 99%
“…We observed that the predicted promoter sequence upstream to the seven genes activates the reporter gene expression, and it was significantly higher in media with limited zinc or iron when assessed in the E. coli surrogate system. Although the E. coli-based analysis may not be ideal for assessing an E. chaffeensis on April 22, 2021 by guest http://jb.asm.org/ Downloaded from promoter function, this heterologous system is currently the best means of investigating the bacterial gene regulation considering the lack of desirable genetic tools for the pathogen (43)(44)(45)(46)(47)(48)(49)(50). Assessment of the effect of promoter deletion analysis suggested that one or more of the putative DNA binding motifs within the sequence respond to zinc or iron depletion.…”
Section: Discussionmentioning
confidence: 99%